2018
DOI: 10.1080/03639045.2018.1526186
|View full text |Cite
|
Sign up to set email alerts
|

Brain targeting of chitosan-based diazepam mucoadhesive microemulsions via nasal route: formulation optimization, characterization, pharmacokinetic and pharmacodynamic evaluation

Abstract: The brain uptake of diazepam from chitosan-based MMEs via nasal route is significantly high compared to i.v route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 40 publications
0
8
0
8
Order By: Relevance
“…Ramreddy et al [153] prepared mucoadhesive microemulsions for nasal delivery of diazepam, the benzodiazepine agent most commonly applied in seizure emergencies. The investigated mucoadhesive microemulsions were composed of oleic acid, Tween ® 80, propylene glycol, water, and chitosan.…”
Section: Epilepsymentioning
confidence: 99%
“…Ramreddy et al [153] prepared mucoadhesive microemulsions for nasal delivery of diazepam, the benzodiazepine agent most commonly applied in seizure emergencies. The investigated mucoadhesive microemulsions were composed of oleic acid, Tween ® 80, propylene glycol, water, and chitosan.…”
Section: Epilepsymentioning
confidence: 99%
“…Numerous studies exposed ex vivo sheep, goat, or porcine nasal mucosa or toad palate to nanoparticles for 0.5–24 h and used light microscopy to assess H&E stained tissue morphology. Most studies showed no gross morphological or histological changes (Abdelbary & Tadros, 2013; Acharya et al, 2013; Bahadur & Pathak, 2012; Devkar et al, 2014; Gaba et al, 2019; Gao et al, 2006; Haider et al, 2018; Jani et al, 2019; Patel, Patel, et al, 2013; Praveen et al, 2019; Ramreddy & Janapareddi, 2019; Sawant et al, 2016; Shah et al, 2015; Shah et al, 2021; Sood et al, 2014; Tzeyung et al, 2019; Upadhyay et al, 2017). In a more extensive study, porcine olfactory epithelium mounted in a vertical Franz diffusion chamber showed tissue damage that was greater after exposure to an equal number of 20, than 100, than 200 nm chitosan‐coated polystyrene particles (Mistry et al, 2015).…”
Section: Intranasal Nanoparticle Adverse Effects Assessmentmentioning
confidence: 99%
“…Під час лікування захворювань нервової системи, необхідно переконатися, що шлях введення ЛЗ забезпечує максимально високу біодоступність діючої речовини в відділі ЦНС (головному мозку), що грає ключову роль в патогенезі захворювання. Таким чином, шлях введення при лікуванні ТР має забезпечити максимально повне надходження діючої речовини до залучених в патогенезі відділів головного мозку, таких як мигдалевидне тіло (corpus amygdaloideum), гіпокамп (hippocampus) та таламус (thalamus) [12,13].…”
Section: вступunclassified
“…Далі активна речовина транспортується через крибриформну плиту (lamina cribrosa) нюхальним та трійчастим нервом до нюхальної цибулини (bulbus olfactorius). Потрапивши до нюхальної цибулини, діюча речовина вивільняється в цереброспінальну речовину, якою транспортується до головного мозку, минаючи гематоенцефалічний бар'єр (ГЕБ) [12,13]. При непрямому шляху діюча речовина минаючи епітелій, замість нюхального та трійчастого нервів потрапляє в щільну систему капілярів носової порожнини.…”
Section: вступunclassified
See 1 more Smart Citation